Experimental Infection of Sand Flies by Massilia Virus and Viral Transmission by Co-Feeding on Sugar Meal - Jancarova, Magdalena; Bichaud, Laurence; Hlavacova, Jana; Priet, Stephane; Ayhan, Nazli; Spitzova, Tatiana; Volf, Petr; Charrel, Remi N (Viruses, 2019)
Background: Massilia virus (MASV) is a phlebovirus isolated from Phlebotomus perniciosus in various regions of southwestern Europe. It is closely related to human pathogens such as Toscana virus and sandfly fever Naples virus. The natural cycle of phleboviruses is poorly understood. Indeed, experimental studies demonstrate that transovarial and sexual transmission are not efficient enough for the maintenance of the virus in nature and to date there is no convincing evidence that a species of vertebrates is the reservoir of the virus. Here, we studied various transmission routes of MASV taking advantage of experimental colonies representing different species of sand flies. Methodology/Principal findings: In P. perniciosus, four sources of infection were compared: (i) Virus-seeded larval food to the first instar larvae (L1), or (ii) to the fourth instar larvae (L4), (iii) virus-seeded blood meal to adult females, and (iv) virus-seeded sugar meal to adults of both sexes. From 875 adults emerged from infected L1 and L4, only three were positive. In females infected by bloodmeal the infection rate was high before defecation, then it decreased drastically; MASV RNA was detected in only 5 out of 27 post-defecation. Surprisingly, the most efficient route of infection was observed after intake of virus-seeded sugar meal: 72% of females (79/110) and 52% of males (51/99) were found to be MASV RNA-positive. In addition, MASV-infected sandflies regurgitated virus particules into the sugar drop and MASV RNA was detectable in this drop for at least 24 h after regurgitation. MASV RNA was detected in about one third of the P. perniciosus exposed to this sugar drop contaminated by regurgitation. Sugar meal infection was also tested with six other species of sand flies. In males, there were no significant differences in infection rates when compared to P. perniciosus. In females, most species tested showed high infection rate at the beginning but then significant gradual decrease in infection rate during the experiment. Conclusions/Significance: We present the first description of arboviral infection of a dipteran vector using sugar meal. In all seven sand fly species tested, MASV was detected for two weeks post-infection. Our results showed that MASV can be transmitted between P. perniciosus either through co-feeding or via an infected sugar source such as plant sap. These newly described routes of horizontal transmission may play an important role in the circulation of phleboviruses in nature.
Keywords: Animals; fomity; Fomites; Meals; Insect Vectors; Phenuiviridae; Food Contamination; stravovací zvyklosti; Phlebotomus; cukry; Phlebovirus; Toscana virus; virus transmission; Psychodidae; Lutzomyia; jídla; kontaminace potravin; hmyz - vektory; Feeding Behavior; Sergentomyia; Sugars; zvířata; horečka pappataci; sand fly; Phlebotomus Fever